Identification of factors to reduce accidents due to rockfall in underground mining - Giraldo Paredez, Emiliano Mauro (2016)
The objective of the present study is to identify factors to reduce accidents in mining or other underground excavations, caused by rockfall. To achieve this purpose, the fatal accidents that occurred from 2001 to 2011 were investigated in the prime sources, among others, MINEM, the Ministry of Labor and Employment Promotion and OSINERGMIN. From the information compiled and processed, the corresponding analysis was performed, thus identifying the following factors: a) Type of rock. 87% of fatal accidents occurred in type III and IV rocks. b) Type of support. 45.8% of fatal accidents occurred in unsupported areas and in areas sustained with wood, Split Set and Helical Bars occurred 45.85%. c) Type of work. 59% of fatal accidents occurred in hacking. d) Occupation. 53% of fatal accidents suffered drilling master and / or assistants. e) Work shift. 58% of fatal accidents occurred in day shifts. f) Hours of the day. 41.4% of fatal accidents occurred between 9: 00-12: 00 and 15: 00-18: 00. g) Service time. 54.3% of fatal accidents suffered workers with less than one year of service.